2012
DOI: 10.1038/ng.2481
|View full text |Cite
|
Sign up to set email alerts
|

Dclk1 distinguishes between tumor and normal stem cells in the intestine

Abstract: There is great interest in tumor stem cells (TSCs) as potential therapeutic targets; however, cancer therapies targeting TSCs are limited. A drawback is that TSC markers are often shared by normal stem cells (NSCs); thus, therapies that target these markers may cause severe injury to normal tissues. To identify a potential TSC-specific marker, we focused on doublecortin-like kinase 1 (Dclk1). Dclk1 was reported as a candidate NSC marker in the gut, but recent reports have implicated it as a marker of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
396
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(431 citation statements)
references
References 30 publications
29
396
1
5
Order By: Relevance
“…Xenotransplantation studies in which cell populations were selected based upon (surface) marker expression, revealed LGR5+, CD133 (AC133 epitope), CD44 or CD166 as CSC markers (4,(13)(14)(15)(16)(17)(18)(19). These findings were supported with lineage tracing experiments in genetically defined mouse models (8,(20)(21)(22). However, these studies do not functionally test stem cells in established human cancers.…”
Section: Identification Of Cscssupporting
confidence: 76%
“…Xenotransplantation studies in which cell populations were selected based upon (surface) marker expression, revealed LGR5+, CD133 (AC133 epitope), CD44 or CD166 as CSC markers (4,(13)(14)(15)(16)(17)(18)(19). These findings were supported with lineage tracing experiments in genetically defined mouse models (8,(20)(21)(22). However, these studies do not functionally test stem cells in established human cancers.…”
Section: Identification Of Cscssupporting
confidence: 76%
“…Doublecortin-like kinase 1 was originally described as a marker that was able to distinguish between Dclk1-positive tumor stem cells and Dclk1-negative normal stem cells in the intestine. 74 Later studies confirmed that Dclk1 regulates pluripotency and angiogenic factors via microRNA-dependent mechanisms, and its expression marks a morphologically distinct subpopulation of cells with stem cells properties in pancreatic cancer. 75,76 In this scenario, it is tempting to suggest that chronic adaptation to metformin accelerates the retrogression from a differentiated cancer cell state to a more stem-like state endowed with enhanced migratory capacities (i.e., the "migrating cancer stem cells" concept originally proposed by Thomas Brabletz).…”
Section: P Value Ratiomentioning
confidence: 91%
“…In terms of other stem cell markers, a recent report suggested that Lgr5 + cells in mouse intestinal adenomas acquired the ability for cancerous growth as a stem cell (27). Dclk1 (doublecortin-like kinase 1), which is a candidate marker for intestinal cancer stem cells, did not dramatically differ in expression between diffuse-type GC and MSCs (28).…”
Section: Discussionmentioning
confidence: 99%